Resveratrol protects early brain injury after subarachnoid hemorrhage by activating autophagy and inhibiting apoptosis mediated by the Akt/mTOR pathway. Issue 5 (21st March 2018) - Guo, Dan; Xie, Jiangtao; Zhao, Junjie; Huang, Tingqin; Guo, Xiaoye; Song, Jinning
Abstract : Early brain injury (EBI) plays a key role in determining the prognosis of patients suffering from subarachnoid hemorrhage (SAH). Resveratrol, a natural polyphenol, serves a neuroprotection function on EBI after SAH. However, the potential mechanism of resveratrol on EBI remains to be elucidated. Akt, also known as protein kinase B, and mammalian target of rapamycin (mTOR), the downstream protein of Akt, play key roles in cell survival and apoptosis, cell cycle regulation, and cellular protein homeostasis. In the present study, we examined the effect of resveratrol on EBI and their potential relationship with the Akt/mTOR pathway, autophagy, and apoptosis. Rats received intraperitoneal administration of resveratrol or vehicle immediately after establishing SAH model. We found that mortality and brain edema were significantly lower, whereas the neurological score was higher for resveratrol-treated rats. HE staining showed that resveratrol significantly reduced the neuronal pyknosis and swelling in the resveratrol-treated rats compared with SAH rats. The results were assessed by western blot, reverse transcription-PCR, and immunohistochemistry and immunofluorescence at 24 h after injury to determine changes in the expression of the Akt/mTOR signaling pathway, autophagy, and apoptosis proteins. Western blot analysis showed that the expression of beclin-1, LC3-II, LC3-II/LC3-I, and Bcl-2 was increased in resveratrol-treated rats, whereas the expression of p-Akt, p-mTOR, p62, cleaved caspase-3, caspase-9, and Bcl-2-associated X protein was decreased. Immunohistochemistry analysis of beclin-1, LC3-B treated with resveratrol alone or in combination with 3-methyladenine (autophagy inhibitor) suggested that resveratrol induced the autophagy process and the inhibitor blocked the occurrence of autophagy, and also increased the number of terminal deoxynucleotidyl transferase-mediated digoxigenin-DUTP-biotin nick-end labeling (+) cells. Taken together, these findings indicate that resveratrol exerts neuroprotective effects on EBI after SAH by regulating autophagy and apoptosis mediated by the Akt/mTOR pathway.